2013
DOI: 10.18869/acadpub.johe.2.1.2.20
|View full text |Cite
|
Sign up to set email alerts
|

The association between VO2max and heart rate of casting industry workers

Abstract: Received: August 2013, Accepted: January 2014Background: To establish a balance between work (physical exercise) and human, the aerobic capacity (VO2max) could be used as a measure. Assessing the heart rate in association to physiological symptoms is the most commonly used tool for the assessment of fatigue during physical exercise. This study aimed to investigate the association between the aerobic capacity and the heart rate of workers from the casting industry. Materials and Methods:The subjects were 200 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Moghiseh et al observed the association of VO 2 max and heart rate in casting industry workers .Their results showed that there was strong correlation between heart rate and VO 2 max and revealed that heart rate could be used as a prediction measure to estimate VO 2 max (67) .…”
Section: Ccchristensen Observed the Physiological Responses To Bicymentioning
confidence: 99%
“…Moghiseh et al observed the association of VO 2 max and heart rate in casting industry workers .Their results showed that there was strong correlation between heart rate and VO 2 max and revealed that heart rate could be used as a prediction measure to estimate VO 2 max (67) .…”
Section: Ccchristensen Observed the Physiological Responses To Bicymentioning
confidence: 99%
“…To ensure proper intensity, all patients will be wearing a heart rate monitor (Polar heart rate monitors and physical fitness watches). Since there is a good correlation between VO2 max and HR max [ 52 ], this is a practical method to monitor the internal training load. The maximal heart rate (HR max ) will be measured as the peak heart rate during the final minute of the VO2 max test [ 53 ].…”
Section: Interventionsmentioning
confidence: 99%
“…Balderrama et al [ 16 ] used mathematical models to estimate from HR using a direct method. Furthermore, the following studies [ 17 , 18 ] established a stronger association between HR and , indicating the fact that HR measurements taken during exercise could be used as predictor variables to estimate .…”
Section: Introductionmentioning
confidence: 99%